SULFUR ECOGEOCHEMISTRY OF COAL - Kizil'shtein L.Ya. (My University, 2001)
Sulfur is a major contaminant of atmospheric air resulting mainly from fuel combustion, primarily coal. This paper deals with the ecological aspects of sulfur geochemistry of coal, including the paleogeographic sulfur trends in coal benches, the alteration of sulfur compounds under conditions of short-term, high-temperature heating during fuel combustion, and the character of sulfur concentration fields in atmospheric air. Ecologically hazardous sulfur concentrations of coals are estimated.
Keywords: Coal; Sulfur; Ecology